HUBUNGAN ANTARA ANEMIA DAN PRESTASI BELAJAR DENGAN INDEKS MASSA TUBUH PADA REMAJA PUTRI KELAS VIII DI SURAKARTA - Widhiyastuti, Endang (Jurnal Farmasi (Journal of Pharmacy), 2017)
Adolescents aged 13-15 years old were transition from early adolescence to late adolescence which is a period of identity search so easily affected the surrounding environment. Therefore, adolescents at high risk of nutritional disorders because in adolescents experienced increased nutritional needs, the habit of limiting the consumption of food and consumption patterns that often deviate from the rules of nutrition science.Status nutrition and anemia are factors that affect the development of the brain. Brain damage due to nutritional disturbances leads to cognitive impairment, impaired IQ development and impaired learning abilities that subsequently affect learning achievement. Objective: This study aims to determine the correlation between anemia and learning achievement with body mass index (BMI) in adolescent girls of class VIII in Surakarta. Research method: The research design used was observational with cross sectional approach, the population of junior high school girls 3 and SMP Negeri 7 Surakarta even semester of 2015/2016, aged 13-15 years. Research subjects amounted to 120 taken by random sampling. Data obtained through questionnaire, nutritional status measured by z-score. Anemia was measured by Hb levels using cyanmethemoglobin method. Learning achievement is measured from the final exam score. Furthermore, the collected data is processed by using bivariate analysis. Result of research: The value of r = 0,201, odd ratio 4,255 and p = 0,35, this means there was correlation between anemia with body mass indeks (IMT) in junior high school girl of class VIII in Surakarta. While the relation between learning achievement with IMT class of females VIII obtained r = 0.093 with odd ratio = 0,307 and p = 0999. This means there was no relationship between learning achievement and BMI. Conclusion: There is a significant relationship between BMI with anemia No relation between IMT and learning achievement.